Т.Г.Шевченко і археологія (вступна стаття Т.В.Калініної) - Іванцов, І.О. (Український історичний журнал, 2014)
У рубриці, присвяченій 200-річчю з дня народження Т.Шевченка, редакція
«Українського історичного журналу» вміщує статтю загиблого в 1941 р., за
нацистської окупації Києва, українського радянського історика й археолога І.Іванцова. Уперше ця студія побачила світ в ювілейному збірнику, підготовленому до 125-ї річниці з дня народження Кобзаря. Працю присвячено історичній та археологічній діяльності T.Шевченка під час його роботи в Київській археографічній комісії. Here presented an article “T.H.Shevchenko and archeology”, what prepared for
“In Memory of Taras Shevchenko: An Article Digest to 125-th Anniversary of
Birthday” (published in Kyiv, 1939), what came as result of collective work of
Institute of History and Institute of Literature scientists. Article is dedicated to
historical and archaeological activity of T.Shevchenko, during his work in the Kyiv
Archeographical Commission. Author of that article – talented Ukrainian soviet
historian and archaeologist I.Ivantsov, who was killed during Nazi occupation of
Kyiv in 1941.